Development of an Augmented Reality-Enhanced Interactive E-Module on the Polyhedron Topic to Maximize Learning Styles - Candra Ditasona; Bintang Pratama; Santri Chintya Purba (RANGE: Jurnal Pendidikan Matematika, 2026)
When studying polyhedron, learning sources that are predominantly verbalistic can lead to difficulties in understanding the concept. Learners have diverse learning preferences for absorbing and processing information, known as learning styles. Therefore, learning media is required to accommodate features oriented towards the learning needs of the students encompass text, audio, video, animations, images, and augmented reality. This research aims to develop a valid and suitable e-module on polyhedron for maximizes students’ learning styles. This research is included in the limited research type that only focus-es on the development and validation stages without involving testing. The model supporting this level of this research is proposed by Richey and Klein, wherein the research phase is limited to evaluation. Throughout the research and development phases, the e-module is validated by content and media ex-perts. During the evaluation stage, every element produced in the e-module for flat-sided of three-dimensional shapes is found to be valid and highly suitable for accommodating students learning style. The result allows the identification of how each feature in the e-module supports visual, auditory, and kinesthetic learning styles.